Human ORFeome Version 1.1: A Platform for Reverse Proteomics - Rual, Jean-François; Hirozane-Kishikawa, Tomoko; Hao, Tong; Bertin, Nicolas; Li, Siming; Dricot, Amélie; Li, Ning; Rosenberg, Jennifer; Lamesch, Philippe; Vidalain, Pierre-Olivier; Clingingsmith, Tracey R.; Hartley, James L.; et al. (Genome Research, 2004)
The advent of systems biology necessitates the cloning of nearly entire sets of protein-encoding open reading frames (ORFs), or ORFeomes, to allow functional studies of the corresponding proteomes. Here, we describe the generation of a first version of the human ORFeome using a newly improved Gateway recombinational cloning approach. Using the Mammalian Gene Collection (MGC) resource as a starting point, we report the successful cloning of 8076 human ORFs, representing at least 7263 human genes, as mini-pools of PCR-amplified products. These were assembled into the human ORFeome version 1.1 (hORFeome v1.1) collection. After assessing the overall quality of this version, we describe the use of hORFeome v1.1 for heterologous protein expression in two different expression systems at proteome scale. The hORFeome v1.1 represents a central resource for the cloning of large sets of human ORFs in various settings for functional proteomics of many types, and will serve as the foundation for subsequent improved versions of the human ORFeome.
10.1101/gr.2973604